Guardian For Children Out of Marriage in Marriage (Analysis of Syafi'īyyah Fiqh and Civil law) - Faisal; Nasrullah; Muhammad Wali al-Khalizi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This writing aims to explain the position guardian in marriage according to Fiqh Syafi'īyyah dan Civil Law, as well asto describe guardian for children out of wedlock according to analysis Fiqh Syafi'īyyah and Civil Law.This research includes library research (Library Research). The method used is descriptive analysis research method, the approach used is a normative approach. To assist the preparation of this research the author reads books and books related to the problems to be discussed. The results showed thatposition guardian in marriage according to Fiqh Syafi'īyyah dan Civil law is very important, meaning that at the same time it has the nature of determining the validity of a marriage contract, so that if a marriage contract is carried out by a guardian or his representative, then the marriage contract will be valid, but on the contrary if the marriage contract is not carried out by the guardian or his representative, then The marriage contract is invalid and invalid. So betweenFiqh Syafi'īyyahand Civil Law has the same view regarding position guardian in marriage. The results also show that which become guardian for children out of wedlock according to Fiqh analysis Shafi'īyyah is guardian judge, in this case is the president even though she is a woman, and state officials whose powers are delegated by the president in matters of trustees such as the Minister of Religion and his lowest officials such as the KUA. Whereas according to Civil Law analysis is the biological father of the child provided there is an acknowledgment from the mother and father and is proven by an authentic deed and can be proven based on science and technology.